Evolution of seismic design codes of highway bridges in Chile. Issue 3 (August 2021) - Wilches, José; Santa Maria, Hernán; Leon, Roberto; Riddell, Rafael; Hube, Matías; Arrate, Carlos
Chile, as a country with a long history of strong seismicity, has a record of both a constant upgrading of its seismic design codes and structural systems, particularly for bridges, as a result of major earthquakes. Recent earthquakes in Chile have produced extensive damage to highway bridges, such as deck collapses, large transverse residual displacements, yielding and failure of shear keys, and unseating of the main girders, demonstrating that bridges are highly vulnerable structures. Much of this damage can be attributed to construction problems and poor detailing guidelines in design codes. After the 2010 Maule earthquake, new structural design criteria were incorporated for the seismic design of bridges in Chile. The most significant change was that a site coefficient was included for the estimation of the seismic design forces in the shear keys, seismic bars, and diaphragms. This article first traces the historical development of earthquakes and construction systems in Chile to provide a context for the evolution of Chilean seismic codes. It then describes the seismic performance of highway bridges during the 2010 Maule earthquake, including the description of the main failure modes observed in bridges. Finally, this article provides a comparison of the Chilean bridge seismic code against the Japanese and United States codes, considering that these codes have a great influence on the seismic codes for Chilean bridges. The article demonstrates that bridge design and construction practices in Chile have evolved substantially in their requirements for the analysis and design of structural elements, such as in the definition of the seismic hazard to be considered, tending toward more conservative approaches in an effort to improve structural performance and reliability for Chilean bridges.